Kenya National Safety Net Program for Results : Integrated Fiduciary Assessment - World Bank (Washington, DC, 2013)
The Government of Kenya (GoK) has a number of well-established social insurance schemes and safety net programs, but their coverage has tended to be low and their effectiveness limited. The coverage of cash transfer programs has grown significantly but remains low in comparison with the size of the population in need. This assessment uses the draft guidance notes on Program-for-Results (PforR) operations prepared by the Operations Policy and Country Services (OPCS) department of the World Bank. The assessment reviews the fiduciary aspects of the government's national safety net program. According to this assessment, the strengths include: (i) sector-wide planning and budgeting through the Sector Working Groups (SWGs), the Medium-term Planning (MTP) framework, and the Medium-term Expenditure Framework (MTEF); (ii) increasing computerization through the Integrated Financial Management Information System (IFMIS); (iii) current efforts to develop and roll out a single registry linked to the Management Information Systems (MISs) for the five cash transfer programs; (iv) the ongoing development and intended roll out of program MISs for the Cash transfer (CT) programs implemented by the department of gender and social development in the Ministry of Gender, Children, and Social Development (MGCSD); (v) the upgrading of the MIS for the CT for Orphans and Vulnerable Children (CT-OVC) and the Hunger Safety Net Programme (HSNP); (vi) independent external audit arrangements by the Kenya National Audit Office (KENAO); and (vii) the fact that the procurement performance of the CT programs will have little or no impact on the implementation of the program. This paper is structured as follows: chapter one gives background and the program's institutional arrangements; chapter two presents program's fiduciary performance and significant fiduciary risks; chapter three focuses on fraud and corruption; chapter four gives institutional arrangements; and chapter five presents mitigating measures.